The Neurobiology of Cognition in the Age of Artificial Intelligence: From Synaptic Plasticity to Cognitive Mapping - Ikrar, Taruna; Sophian, Alfi (Journal of NeuroPhilosophy, 2025)
Cognition emerges from complex interactions among molecular, cellular, and network-level processes in the brain that allow adaptive representation, reasoning, and behavioral regulation. Recent advances in neurobiology, combined with artificial intelligence (AI) and computational modeling, have illuminated previously inaccessible aspects of cognitive mechanisms—ranging from synaptic plasticity to large-scale cognitive mapping. This review explores how neural substrates underpin core cognitive processes such as attention, memory, and prediction, and how these biological architectures inspire AI systems through neuro-symbolic and neuromorphic approaches. We examine the dynamic relationship between predictive coding, hierarchical cortical networks, and consciousness as a distributed emergent property. Furthermore, new insights from connectomics, optogenetics, and neural decoding provide unprecedented clarity about the biophysical basis of cognition. The convergence between neurobiology and AI offers not only models of intelligence but also novel frameworks to understand self-referential cognition, agency, and ethical implications of synthetic minds. Ultimately, the neurobiology of cognition is entering a transformative era where understanding the brain’s logic informs both human enhancement and machine consciousness.